KELECAKAN DAN KEKUATAN TEKAN BETON BERBASIS ABU TERBANG SEBAGAI PENGGANTI SEMEN DAN BATU APUNG UNTUK PENGGANTI AGREGAT KASAR - Muhammad Sofyan; Ade Okvianti Irlan; Jansen Zadrak Korobu; Abdul Rokhman (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2022)
Concrete's drawback is its low tensile strength and heavy weight, which may exceed 2400 kg/m3. The significance of self-weight in building construction is essential, particularly when dealing with seismic loads. The larger the inertial force from the weight of the structure itself, the greater the inertial force from the weight of the building itself, therefore lightweight concrete can provide an opportunity to lower its own weight with a smaller unit weight of 1850 kg/m3. Fly ash was employed as a substitute for cement in this investigation, while pumice was used as a substitute for coarse aggregate. The goal of this research was to establish the unit weight, compressive strength, and workability/slump value of concrete. In this investigation, 30% of the fly ash was utilized. Pumice is determined at 0%, 5%, 10%, and 15% of the weight of coarse aggregate. The SN sample has the highest slump value of 8.8. However, the slump value continued to fall with the addition of pumice. The use of larger pumice stone results in   a reduction in the volume weight of concrete up to 1845 kg/m3, permitting it to be classified as lightweight concrete. Pumice has been demonstrated to diminish strength by 11% on average for every 5% replacement